Cell pyroptosis in picornavirus and its potential for treating viral infection. Issue 8 (6th May 2022) - Wang, Zheng; Yu, Haolin; Zhuang, Wenyue; Chen, Jingxuan; Jiang, Yi; Guo, Zhicheng; Huang, Xiaotian; Liu, Qiong
Abstract: Cell pyroptosis has received increased attention due to the associations between innate immunity and disease, and it has become a major focal point recently due to in‐depth studies of cancer. With increased research on pyroptosis, scientists have discovered that it has an essential role in viral infections, especially in the occurrence and development of some picornavirus infections. Many picornaviruses, including Coxsackievirus, a71 enterovirus, human rhinovirus, encephalomyocarditis virus, and foot‐and‐mouth disease virus induce pyroptosis to varying degrees. This review summarized the mechanisms by which these viruses induce cell pyroptosis, which can be an effective defense against pathogen infection. However, excessive inflammasome activation or pyroptosis also can damage the host's health or aggravate disease progression. Careful approaches that acknowledge this dual effect will aid in the exploration of picornavirus infections and the mechanisms that produce the inflammatory response. This information will promote the development of drugs that can inhibit cell pyroptosis and provide new avenues for future clinical treatment.